Prioritization of vigor QTL-associated genes for future genome-directed Vitis breeding = Priorización de genes asociados a QTLs de vigor para futuros planes de mejoramiento dirigido en Vitis - Hugalde, Ines Pilar; Paolinelli, Marcos; Gomez Talquenca, Sebastian; Walker, M. Andrew; Vila, Hernan; Aguero, Cecilia B.; Riaz, Summaira (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2025)
Vigor control in grapevine may become especially important under climate change. A better understanding of gene-phenotype relationships is required in order to exploit plant genomics for breeding purposes. This research aims to use quantitative trait loci (QTLs) for vigor identified in the progeny from a cross of Ramsey (Vitis champinii) × Riparia Gloire (V. riparia). Genes located 700 kb up and downstream from each QTL position were interro gated for functional enrichment through ShinyGO online tool, based on the gene ontology annotation of Vitis vinifera PN40024. Key biological processes like phloem and xylem development, cell cycle, response to hormones, amino acid transport, tissue development, sugar metabolism, nitrogen transport, and stress/immune responses, showed functional enrichment. Integral response to light and auxin might be required for fine molecular tuning of vegetative growth in Vitis. Fifty out of 1318 candidate genes were prioritized, reducing their amount to a manageable number of candidates genes for further directed breeding strategies.